The Catholic Church’s Resistance to Geothermal Projects in Flores: Rethinking the Role of Religious Institutions in Environmental Justice - Amriani, Nita; Alfian, Andi (Litbang STFT Widya Sasana Malang, 2025)
This study examines the Catholic Church's resistance to a geothermal energy development project in Flores, Indonesia, by highlighting the theological, ecological, and social perspectives that underlie it. This resistance is motivated by concerns about potential environmental damage, health impacts, and threats to the socio-economic well-being of local communities. For the Catholic Church, preserving God's creation is not only a spiritual mandate but also a moral responsibility related to a commitment to sustainable development. This study uses a qualitative approach with a descriptive case study method.Data were collected through interviews and supported by secondary sources such as media reports and relevant academic literature. Through thematic analysis, this study examines various forms of advocacy carried out by the Church, including the use of moral discourse, grassroots mobilization, and collaboration with indigenous communities and environmental organizations. This study also examines how the Church plays a role as a religious institution and social agent in challenging the narrative of state and corporate development that ignores ecological sustainability and community rights. The findings show that the Catholic Church in Flores plays a significant role in shaping public opinion, encouraging community resistance, and influencing policy debates related to geothermal energy.This study contributes to a broader understanding of ecotheology and the role of religion in environmental justice movements. The Church’s resistance reflects a contextual theological response that connects spirituality with social-ecological activism and offers a model for just, sustainable, and inclusive development.